Pendampingan peningkatan Persepsi Konsumen terhadap Cita Rasa dan Branding Produk UMKM "Kedai Rasa" di Kecamatan Banjarsari Surakarta - Tri Wijayanti; Dewi Ekowati; Annisa Ratna Fadilla Purba; Desti Nuryani Sitompul; Ismi Maksalmina; Mohammad Febry Andintias; Triyani, Triyani; Rodhi Anshari (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
Micro, Small and Medium Enterprises (MSMEs) have a strategic role in the Indonesian economy. In the face of increasingly fierce competition, "Kedai Rasa" is faced with various challenges. One of the main challenges is creating a positive consumer perception of the taste of the product while building strong branding. UMKM "Kedai Rasa" is one of the main targets of Community Service (PKM) activities. This research uses descriptive methods with quantitative and qualitative approaches. Overall, Kedai Rasa has succeeded in meeting customer expectations with taste, innovation and adequate portions. To increase satisfaction, Kedai Rasa can continue to innovate its menu, maintain taste consistency, and adapt its offerings to a wider range of customer preferences.